Watching Kinetic Studies as Chemical Maps Using Open-Source Software - Cotte, Marine; Fabris, Tiphaine; Agostini, Giovanni; Motta Meira, Debora; De Viguerie, Laurence; Solé, Vicente Armando (Analytical chemistry (Washington), 2016)
A nonproprietary software package, "PyMca", primarily developed for X-ray fluorescence analysis offers an easy-to-use interface for calculating maps, by integrating intensity (of X-ray fluorescence, as well as any spectral data) over Regions Of Interest (ROI), by performing per pixel operations or by applying multivariate analysis. Here we show that, while initially developed to analyze hyperspectral two-dimensional (spatial) maps, this tool can be beneficial as well to anyone interested in measuring spectral variations over one or two dimensions, these dimensions being time, temperature, and so on. Different possibilities offered by the software (preprocessing, simultaneous analysis of replicas, of different conditions, ROI calculation, multivariate analysis, determination of reaction rate constant and of Arrhenius plot) are illustrated with two examples. The first example is the Fourier transform infrared spectroscopy (FTIR) follow-up of the saponification of oil by lead compounds. The disappearance of reagent (oil) and formation of products (lead carboxylates and glycerol) can be easily followed and quantified. The second example is a combined extended X-ray absorption fine structure (EXAFS), diffuse reflectance infrared Fourier transform spectroscopy (DRIFT), and mass spectroscopy (MS) analysis of RhAl2O3 catalyst under NO reduction by CO in the presence of O2. It is possible to appreciate, in a single shot, Rh particles' structure and surface changes and gas release and adsorption in the reaction conditions.